On-line control of crystal deflector quality; Nuclear Instruments and Methods in Physics Research Section B: Beam Interactions with Materials and Atoms; Vol. 266, iss. 17 - Gogolev A. S. Aleksey Sergeevich; Potylitsyn A. P. Alexander Petrovich; Taratin A. M.; Tropin Yu. S. (2008, 2008)
An on-line control method of crystal deflector quality based on parametric X-ray radiation is proposed. The technique considered will allow information to be received about the state of the deflector crystal structure directly in the local interaction area of the beam and the crystal.